Functional constipation and posture in defecation - Tanjung, Fahrul Azmi; Supriatmo, Supriatmo; Sinuhaji, Atan Baas; Hakimi, Hakimi (Paediatrica Indonesiana, 2013)
Background Functional constipation is often a consequence of habitual bowel elimination while sitting on common toilet seats. A considerable proportion of the population with n ormal bowel movement frequency has difficulty emptying their bowels. The principal cause of this problem may be the obstructive nature of the rectoanal angle and its relationship to the posture normally used in defecation. Objective To assess the relationship between functional constipation with the posture (sitting vs squatting) during defecation in children. Methods We conducted a cross-sectional study in November 2010. Participants aged 12- 15 years were selected consecutively from a junior high school in Medan . Parents and children filled questionnaires and were interviewed. Functional constipation was assessed based on the Rome III criteria. Results Sixty-five students enrolled in the study. There was no statistically significant diffe rences in subjects' characteristics. T here was a significant correlation between functional constipation with posture during defecation in children (RR= 0.06, 95%CI 0.02 to 0.25; P=0.0001). Functional constipation was more likely occured in children with sitting (12/20) th an squatting posture (4/45) during defecation. Conclusion We found th at posture in defecation is correlated to functional con stipation in children.